PERJANJIAN PERDAMAIAN UNTUK MENCIPTAKAN KONSEP CORPORTAE RESQUE DALAM RESTRUKTURISASI SEMI PUBLIK INSOLVENCY LAW DI ERA BISNIS MODERN - Putri Maha Dewi; Ismawati Septiningsih; Itok Dwi Kurniawan (Fakultas Hukum Universitas Sebelas Maret, 2023)
Many companies face the threat of difficulty paying their debts to their creditors. There are many reasons the debtor has not paid off the debt, including being unable to pay off the debt that has been given at all, the debt that has been paid is still insufficient for the debt bill, being late in paying the debt, or paying the debt but not in accordance with what has been agreed. The reconciliation plan in the PKPU contains one of which is the debtor's plan to restructure his debts in accordance with the principle of business continuity, which most often is rescheduling, regulated in Article 265 of Law Number 37 of 2004 concerning Bankruptcy. The parties are free to determine the content of the peace plan, the freedom of the content of this peace plan is known as the principle of freedom of contract. The peace agreement which has been ratified by the court, then the reconciliation has binding legal force for the Debtor and the Creditors.